Eksplorasi fitogenik daun kari Murraya koenigii L. Spreng sebagai pakan fungsional berkelanjutan: kajian literatur - Nyimas Popi Indriani; Iin Susilawati; Lizah Khairani; Mansyur; Romi Zamhir Islami (Fakultas Pertanian Universitas Majalengka, 2026)
Curry leaf plant (Murraya koenigii) is an aromatic plant from the Rutaceae family found widely in South and Southeast Asia. Used as a culinary spice, curry leaves have great potential as phytogenics (bioactive compounds), natural plant-based used in animal feed to improve health and productivity. The use of phytogenics is a safer alternative to antibiotic growth promoters (AGPs) because it can reduce the risk of microbial resistance and drug residues in livestock products. Bioactive compounds in curry leaves include carbazole alkaloids, flavonoids, saponins, tannins, phenolics, terpenoids, and essential oils, which act as antioxidants, antimicrobials, anti-inflammatories, immunomodulators, and metabolic promoters. Phytochemical analysis shows that alkaloids are dominant, accompanied by flavonoids, saponins, phenolics, and tannins, which contribute to their biological activity. Curry leaf extracts and powder help control pathogenic microflora in livestock digestive tract and reduce the risk of infection. Curry leaves can also suppress inflammation and boost the immune system by increasing antioxidant capacity and reducing oxidative stress. From a sustainability perspective, curry plants are easy to cultivate in tropical regions, can be harvested repeatedly, and have a relatively low environmental impact. However, further research is needed on optimal dosage, long-term safety, molecular mechanisms of action, and the standardization of ingredient quality and regulatory standards for their use as feed additives. In general, the curry leaves are a local phytogenic resource with multifunctional activities, potentially improving livestock health and productivity, and supporting sustainable and environmentally friendly livestock systems.